Legal Policy of Formalization of Islamic Sharia in Indonesia - Najib, Muhammad Ainun (Universitas Islam Indonesia, 2020)
There are always some Indonesians that discourse and fight for the idea of Islamic state and formalization of sharia. Their effort through constitutional channels gains some success, like 1974 Marriage Act, 1989 Religious Courts Act, and Compilation of Islamic Law (KHI). Sharia formalization is strongly influenced by political interests of the rulers which are inseparable from the socio-political context of its application. This article discusses on how the change of political circumstance has influenced the formalization of sharia in various eras of Indonesia’s government and political factors that influence the dynamic of the formalization of sharia. By using socio-legal research, this study reveals that the formalization of sharia in Indonesia experienced ups and downs according to the relation between state and religion applied by each regime. The formalization is more influenced by the relationship between Islam and the state. When Islamic camp got formalist in character, the formalization was difficult. but if a cultural character was used, formalization became easier. Furthermore, the formalization of sharia by the rulers at least has political, administrative, and contextualization interests.Keywords: Formalization; Sharia; Islamic Struggle; InterestsPolitik Hukum Formalisasi Syariah Islam Di IndonesiaAbstrakSelalu ada beberapa orang Indonesia yang mewacanakan dan memperjuangkan gagasan negara Islam dan formalisasi syariah. Upaya mereka melalui jalur konstitusional memperoleh beberapa keberhasilan, seperti UU Perkawinan 1974, UU Peradilan Agama 1989, dan Kompilasi Hukum Islam (KHI). Formalisasi syariah secara kuat dipengaruhi oleh kepentingan politik penguasa yang tidak terlepas dari konteks sosial dan politik penerapannya. Artikel ini membahas tentang bagaimana perubahan situasi politik mempengaruhi formalisasi syariah di pelbagai era pemerintahan Indonesia dan faktor-faktor politik yang mempengaruhi dinamika formalisasi syariah. Dengan menggunakan penelitian socio-legal, penelitian ini mengungkapkan bahwa formalisasi syariah di Indonesia mengalami pasang surut sesuai dengan relasi negara dan agama yang diterapkan oleh masing-masing rezim. Formalisasi tersebut lebih banyak dipengaruhi oleh hubungan antara Islam dan negara. Ketika kubu Islam berwatak formalis, formalisasi menjadi sulit. Namun, jika basis budaya digunakan, maka formalisasi menjadi lebih mudah. Selanjutnya, formalisasi syariah oleh penguasa setidaknya memiliki kepentingan politik, administratif, dan kontekstual.Kata kunci: Formalisasi, Syariah, Perjuangan Islam, Kepentingan